The impact of oil palm revitalization partnership at PT. Brahma Bina Bakti to farming participants revenues in Sekernan District, Muaro Jambi Regency. (October 2019) - Ernawati, HD; Fathoni, Zakky; Wahyuni, Ira; Fauzia, Gina; Tamba, Rio Swantomy
Abstract: This study aims to determine the application of partnership Plantation Revitalization Program (PRP) and reviewing farm income of palm oil farmers participating in a partnership with PT. Brahma Bina Bakti in District Sekernan. This research was conducted in the village of Suak Putat, Tanjung Lanjut with the study of side income. In its application, the pattern of development of the garden (70%: 30%) is 70% of the land to farmers and 30% of the land to the company. While the pattern of results (30%: 70%) is of the total sales value of farmers' land TBS then 70% cut by the company through cooperatives and 30% delivered to farmers through farmer group administrator. This pattern of results is done through credit/interest paid. The result of the calculation is known that the average income of farmers at the farm level is Rp 6, 291, 397.04 / ha/year while the rate of KUD is Rp 6, 831, 633.66 / ha/year. Income farming palm at the farmer level is smaller than the palm farm income at the level of KUD. This is caused by differences in the structure of production costs where other costs are not covered sacrificed farmers and cooperatives that the cost of medicines, family workers and agricultural tools.